A Miniaturized Patch Antenna Designed and Manufactured Using Slot's Technique for RFID UHF Mobile Applications - Younes El Hachimi; Yassine Gmih; El Mostafa Makroum; Abdelmajid Farchi (Institute of Advanced Engineering and Science, 2018)
In this research work, a novel compact antenna with rectangular slots is presented for radio frequency identification (RFID) handled applications in the ultrahigh frequency (UHF) band that can be manufactured and integrated into RFID readers without difficult. A prototype demonstrating the aforementioned features was constructed and measured. The proposed antenna is fed by 50-Ω coaxial cable and printed on a 1.6mm thick FR4 substrate which has a small size and occupies a volume of 68×66 ×1.6mm3. The patch, the feed-line and ground plane are made of PEC (Perfect Electric Conductor) with a thickness of 0.035 mm. Measured results indicate that the proposed antenna has a good impedance matching characteristic ranging from 889 to 939MHz, which covers the USA RFID-band (902–928MHz), the Chinese RFID-operating-band (920–924.5MHz), and the Korea and Japan RFID-band (917–923.5MHz). These results were achieved by the insertion of slots in the compact structure of the antenna. The electromagnetic simulators HFSS (High Frequency structure simulator) and CST (Computer Simulation Technology) microwave studio were used for the design, modeling and simulation of the antenna. The focus of the study of our antenna was on the parameters of return loss, bandwidth, Voltage Standing Wave Ratio (VSWR), input impedance and gain.